Rivulus mahdiaensis, a new killifish from central Guyana (Cyprinodontiformes: Rivulidae) - Suijker, W. H.; Collier, G. E. (Zootaxa, 2006)
Rivulus mahdiaensis, new species, was found in a small creek, a tributary of the Potaro River, near Mahdia, central Guyana. Males differ from all other species of the genus Rivulus by possessing elongate anal and dorsal fins, and an extremely large and lyre-shaped caudal fin with long extensions. Females differ from other species of the genus, except for three closely related species, by the presence of a narrow, dark longitudinal band on the sides. R. mahdiaensis possesses a unique karyotype (2n=38) among members of this group. Comparison of mitochondrial DNA sequences place this species as a member of a monophyletic clade which includes other small species from the Guyana shield and adjacent areas of northeastern South America.Rivulus mahdiaensis, una nueva especie, se encontró en un pequeño arroyo tributario del Rio Potaro cercano a la localidad de Madhia , en la Guyana Central. Los machos difieren de todas las otras especies del género Rivulus por sus aletas anales y dorsales extremadamente largas y una aleta caudal en forma de lira con largos filamentos en sus extremos. Las hembras difieren de otras especies del Género , excepto por tres especies relacionadas, por la presencia de una estrecha y obscura banda longitudinal en ambos lados. R. mahdiaensis posee un único cariotipo (2n=38) entre los miembros de este grupo. Comparando la secuencia de DNA mitocondrial podemos situar a esta especie como un miembro de un clado monofilético que incluye otras pequeñas especies de la región de la Guyana y áreas vecinas del Noroeste de Sudamérica